2005
DOI: 10.1097/01.mib.0000178261.88356.67
|View full text |Cite
|
Sign up to set email alerts
|

Oro-Facial Granulomatosis: Crohnʼs Disease or a New Inflammatory Bowel Disease?

Abstract: Endoscopic and histologic intestinal abnormalities are common in patients with OFG with no gastrointestinal symptoms. Younger patients with OFG are more likely to have concomitant intestinal involvement. In these patients, granulomas are more frequent in endoscopic biopsies than reported in patients with documented CD. OFG with associated intestinal inflammation may represent a separate entity in which granulomatous inflammation occurs throughout the gastrointestinal tract in response to an unknown antigen or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
105
4
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 27 publications
(26 reference statements)
3
105
4
4
Order By: Relevance
“…In this regard, Scully et al 8 found that 37% of patients, having no intestinal symptoms but with clinical evidence of oral CD, had demonstrable intestinal disease. Sanderson et al 5 also found that endoscopic and histologic intestinal abnormalities were common in patients with OFG and without gastrointestinal symptoms. Therefore, dermatologists should consider the presence of an OFG as a possible early sign suggestive of another inflammatory intestinal disorder, such as CD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, Scully et al 8 found that 37% of patients, having no intestinal symptoms but with clinical evidence of oral CD, had demonstrable intestinal disease. Sanderson et al 5 also found that endoscopic and histologic intestinal abnormalities were common in patients with OFG and without gastrointestinal symptoms. Therefore, dermatologists should consider the presence of an OFG as a possible early sign suggestive of another inflammatory intestinal disorder, such as CD.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a question has been posed to determine whether OFG is a manifestation of a separate and specific inflammatory bowel disease 5 . Other authors also suggested that OFG is a descriptive term and the specific cause of these lesions is unknown 6 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated intestinal granulomatous inflammation in up to 60% of patients with OFG who have no gut symptoms. 2 The exact relevance of the latter finding is not clear, particularly as the majority of patients remain free from gastrointestinal symptoms over many years of follow-up. Whether this particular subgroup of patients with asymptomatic gut involvement should be labeled as oral CD or as a separate entity remains open to debate.…”
mentioning
confidence: 97%
“…Do najczęściej wystę-pujących manifestacji nieswoistych zapaleń jelit w jamie ustnej należą: rozlany obrzęk warg, policzków, powiększone brodawki dziąsłowe, nadżerki i owrzodzenia warg z lub bez współistnie-jącego zapalenia kątów ust oraz pęknięcia warg w linii środkowej, a także zmiany aftopodobne, zapalenia dziąseł i zanikowe zapalenia błony śluzo-wej oraz grzybice jamy ustnej i opryszczka nawracająca [5][6][7][8]. Ponieważ zmiany te w 5-10% przypadkach zachorowań mogą wyprzedzać typową manifestację kliniczną [1], badanie jamy ustnej jest uważane za istotny aspekt diagnostyczny u dzieci z podejrzeniem nieswoistego zapalenia jelit.…”
unclassified